Outcomes and patterns of use of Radium-223 in metastatic castration-resistant prostate cancer - Anido-Herranz, Urbano; Fernandez-Calvo, Ovidio; Ruiz-Bañobre, Juan; Martinez-Breijo, Sara; Fernandez-Nuñez, Natalia; Nogareda-Seoane, Zulema; Garrido-Pumar, Miguel; Casas-Nebra, Javier; Muñiz-Garcia, Gloria; Portela-Pereira, Paula; Gomez-Caamaño, Antonio; Perez-Fentes, Daniel Adolfo; et al. (Frontiers in Oncology, 2024)
Introduction Radium-223 dichloride (Ra-223) is recommended as a treatment option for metastatic castration-resistant prostate cancer (mCRPC) patients with symptomatic bone metastases and no visceral disease, after docetaxel failure, or in patients who are not candidates to receive it. In this study, we aimed to ambispectively analyze overall survival (OS) and prognostic features in mCRPC in patients receiving Ra-223 as per clinical routine practice and identify the most suitable treatment sequence. Patients and methods This study is observational, multicentric, and ambispective. Eligibility criteria included mCRPC patients treated with Ra-223, with an Eastern Cooperative Oncology Group (ECOG) performance status of 0–2, without visceral metastases, and no more than three cm involved lymph nodes. Results A total of 145 patients were included; the median age was 73.97 years, and a Gleason score of more than or equal to 7 in 61 (48%) patients; 73 (81%) had previously received docetaxel. The most important benefit was reached by those patients who received Ra-223 in the second-line setting, with a median OS of 17 months (95% CI, 12–21), and by patients who received six cycles of treatment, with a median OS of 19 months (95% CI, 14–21). An alkaline phosphatase (ALP) decrease was also identified as a prognosis marker. When performing the multivariate analysis, the time to develop castration-resistant disease longer than 24 months was the most important prognostic factor to predict the evolution of the patients receiving Ra-223. Ra-223 was well tolerated, with thrombocytopenia, anemia, and diarrhea being the main adverse events. Conclusion There is a benefit for those patients who received Ra-223 in the second-line setting, regardless of prior use of docetaxel. In addition, a survival benefit for patients presenting with a decline in ALP was observed.